Optimizing Problem-Solving Skills in First Grade: A Project-Based Learning Model Enhanced by Lesson Study at Sekolah Dasar Unggulan Hamzanwadi - Sarah Maulida, Siti; Banuharli, Sastrawan; Saparwadi, Saparwadi; Nursali, Nursali; Sanuardi, Sanuardi; Kartika Murni, Rita; Nuraini, Nuraini (IJE : Interdisciplinary Journal of Education, 2024)
This research examines the implementation of School-Based Lesson Study at Sekolah Dasar Unggulan Hamzanwadi with a focus on improving the quality of teacher learning. Field data indicates that some students have not reached the target for learning quality, especially in group problem-solving skills. The research is focused on improvement through planning, implementation, and evaluation cycles (Plan-Do-See). Cycle I focuses on visual arts learning about shapes, while Cycle II emphasizes group problem-solving through practical baking activities. Lesson Study at Sekolah Dasar Unggulan Hamzanwadi has advantages in encouraging student interaction and fostering creativity but needs to address drawbacks such as a relatively long implementation time and student resistance to group learning.